The crucifixion : understanding the death of Jesus Christ - Rutledge, Fleming (Grand Rapids, Michigan : William B. Eerdmans Publishing, 2015)
Few treatments of the death of Jesus Christ have made a point of accounting for the gruesome, degrading, public manner of his death by crucifixion, a mode of execution so loathsome that the ancient Romans never spoke of it in polite society. Rutledge probes all the various themes and motifs used by the New Testament evangelists and apostolic writers to explain the meaning of the cross of Christ. She shows how each of the biblical themes contributes to the whole, with the Christus Victor motif and the concept of substitution sharing pride of place along with Irenaeus's recapitulation model.
Introduction -- Part I. The Crucifixion : -- 1. The primacy of the cross -- 2. The godlessness of the cross -- 3. The question of justice -- Bridge chapter: Anselm reconsidered for our time -- 4. The gravity of sin -- Part II. The Biblical Motifs : -- Introduction to part 2: Motifs of the crucifixion -- 5. The Passover and the Exodus -- 6. The blood sacrifice -- 7. Ransom and redemption -- 8. The great assize -- 9. The apocalyptic war: Christus Victor -- 10. The descent into hell -- 11. The substitution -- 12. Recapitulation -- Conclusion: Condemned into redemption: the rectification of the ungodly.
Includes bibliographical references and indexes.
Online resource (Proquest, viewed November 8, 2019).
Master record variable field(s) change: 650
Keywords: Jesus Christ -- Crucifixion; Jesus Christ; Atonement; RELIGION -- Christian Theology -- Christology; Atonement; Crucifixion of Jesus Christ; Korsfästelsen.; Electronic books